BIG DATA AND METAVERSE TOWARD BUSINESS OPERATIONS IN INDONESIA - Depari, Genesis Sembiring; Efin Shu; Indra, Indra (Jurnal Ekonomi, 2022)
The rapid growth of information and technology recently brings new opportunities in business operational. An optimal used of resources may leads into business efficiency and therefore minimizing operational cost. Moreover, new opportunities are also revealed by creating more innovations in business. Metaverse gain its popular name firstly in public awareness in October 2021, when Facebook, Inc. renamed it "Meta" and announced a multi-billion-dollar investment in Metaverse technology. In Indonesia, the concept of big data and metaverse technology is still growing and keep attracting attention of many researchers, academics, and business practitioners. Besides the promised opportunities, these technologies are facing several obstacles in adoption. Lack of available talents and infrastructure still two dominant topics to be discussed. Fortunately, Indonesian government shows a serious effort on pursuing a better infrastructure and available talents through providing supports and quality training.